Expresión yxorx*!z
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
y⊕(x∧¬z)=(y∧z)∨(y∧¬x)∨(x∧¬y∧¬z)
(y∧z)∨(y∧¬x)∨(x∧¬y∧¬z)
(y∧z)∨(y∧(¬x))∨(x∧(¬y)∧(¬z))
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(x∨y)∧(y∨¬y)∧(y∨¬z)∧(x∨y∨z)∧(x∨y∨¬x)∧(x∨z∨¬x)∧(y∨z∨¬y)∧(y∨z∨¬z)∧(y∨¬x∨¬y)∧(y∨¬x∨¬z)∧(z∨¬x∨¬y)∧(z∨¬x∨¬z)
(x∨y)∧(y∨(¬y))∧(y∨(¬z))∧(x∨y∨z)∧(x∨y∨(¬x))∧(x∨z∨(¬x))∧(y∨z∨(¬y))∧(y∨z∨(¬z))∧(y∨(¬x)∨(¬y))∧(y∨(¬x)∨(¬z))∧(z∨(¬x)∨(¬y))∧(z∨(¬x)∨(¬z))
Ya está reducido a FND
(y∧z)∨(y∧¬x)∨(x∧¬y∧¬z)
(y∧z)∨(y∧(¬x))∨(x∧(¬y)∧(¬z))
(y∧z)∨(y∧¬x)∨(x∧¬y∧¬z)
(y∧z)∨(y∧(¬x))∨(x∧(¬y)∧(¬z))
(x∨y)∧(y∨¬z)∧(z∨¬x∨¬y)
(x∨y)∧(y∨(¬z))∧(z∨(¬x)∨(¬y))